Ацетилювання α-тубуліну впливає на зміни білкового мікрооточення мікротрубочок при розвитку аутофагії в клітинах тютюну - Литвин, Д.І.; Федина, В.Д.; Ємець, А.І.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. Microtubules (MTs) play an important role in the regulation of autophagy development in yeast and animal cells. MTs participate in maturation and traffic of autophagosomes through their dynamic state changes and post-translational modifications of tubulin, including acetylation. But the role of the plant cytoskeleton remains unclear in this field of cellular functions. We investigated the involvement of plant MTs in the development of starvation-induced autophagy via tubulin acetylation. Methods. We subjected BY-2 tobacco cells to metabolic stress induced by prolonged cultivation, and analyzed interrelation of autophagy development and tubulin acetylation and its microinvironement. Results. Development of autophagy was strongly accompanied by α-tubulin acetylation in tobacco BY-2 cells. This post-translational modification was caused by changes in the MTs microenvironment that was revealed via co-immunoprecipitation assay. The termination of autophagy led to the development of nucleosomal DNA fragmentation and decreases in α-tubulin acetylation. Conclusions. Our work indicates the role of the functional state of the cytoskeleton in the mediation of plant autophagy via changes in the tubulin post-translational modifications and its microenvironment.